Are health care systems insensitive to needs of suicidal patients in times of conflict? The Kashmir experience - Shiekh Shoib; Yasir H Rather; Akash Yousf Khan; Muhammad Maqbool Dar; Abdul Wahid Khan; Arshad Hussain; Zaid Ahmad Wani (Mental Illness)
Suicide and attempted suicide is an important health issue and the number of people who die of suicide exceeds that of conflicts. Kashmir has been suffering from a low intensity war since last 20 years in which thousands have been killed or injured. There has been phenomenal increase in cases of psychological disorders along with suicide and and suicide attempters. Suicide in a conflict zone is viewed with indifference due to focus on the physical part of trauma. Difficulties faced by the suicidal patient and his attendants are seldom highlighted. 1408 patients who reported to emergency room for suicide attempt from 2000 to 2008 were taken for the study. All the patients underwent the hospital protocol for poisoning management. Patients were subjected to detailed psychiatric evaluation and questions were specifically asked about the difficulties encountered during management. Most of the cases were females with 92.11% belonging to the Muslim religion. 76.20% cases were from a rural background. 32.5% had been referred because of the lack of specific antidotes. Forty-three percent required arrangement of transportation by their own family members. Fifty-seven percent had been stopped for security checks along the way. Seventy-three percent felt that the attitude of the staff hostile. Twenty-three percent of patients had to share a bed. Almost all patients were questioned by security agencies within the hospital. More than 68% patient reported hostility amongst their neighbors. Suicidal poisoning is a significant health problem in Kashmir and management of these cases is fraught with difficulties across the spectrum of health care. Educating the doctors at primary care about first aid, improvement in community services followed by long term resolution of the conflict would go some way in alleviating the difficulties faced by a suicidal patient and his family in a conflict zone.